2021
DOI: 10.18632/oncotarget.28040
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the MAP2K7-JNK pathway with 5Z-7-oxozeaenol induces apoptosis in T-cell acute lymphoblastic leukemia

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive pediatric leukemia with a worse prognosis than most frequent B-cell ALL due to a high incidence of treatment failures and relapse. Our previous work showed that loss of the pioneer factor KLF4 in a NOTCH1-induced T-ALL mouse model accelerated the development of leukemia through expansion of leukemia-initiating cells and activation of the MAP2K7 pathway. Similarly, epigenetic silencing of the KLF4 gene in children with T-ALL was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Although the role of JNK activity in T-ALL remains largely unknown, we have previously shown that JNK activation is required for upregulating interleukin 8 expression induced by CXCL12 in primary T-ALL cells [18]. Moreover, inhibition of JNK activity has been shown to lead to cell cycle arrest and apoptosis [83,84]. Our data showing hyperphosphorylation of JNK in T-ALL cell lines suggests a role for JNK in sustaining leukemia.…”
Section: Discussionmentioning
confidence: 58%
“…Although the role of JNK activity in T-ALL remains largely unknown, we have previously shown that JNK activation is required for upregulating interleukin 8 expression induced by CXCL12 in primary T-ALL cells [18]. Moreover, inhibition of JNK activity has been shown to lead to cell cycle arrest and apoptosis [83,84]. Our data showing hyperphosphorylation of JNK in T-ALL cell lines suggests a role for JNK in sustaining leukemia.…”
Section: Discussionmentioning
confidence: 58%
“…Comparative analysis of MAP2K7-JNK inhibitors against the KOPT-K1 cell line demonstrated that OTSSP167 (IC 50 12 nM) is more potent than 5Z-7-Oxozeaenol (IC 50 0.81 μM) and JNK-IN8 (IC 50 8.55 μM) ( Figure 1 E). 11 , 16 This difference in potency was also evident in other cell lines, such as ALL-SIL and RPMI-8402 ( supplemental Figure 1 ). Collectively, the compound OTSSP167 emerges as a powerful antileukemic agent in T-ALL.…”
Section: Resultsmentioning
confidence: 65%
“… 15 Although more potent than JNK inhibitors, 5Z-7-oxozeaenol toxicity limited the capacity of this compound to control leukemia efficiently in preclinical mouse models. 16 …”
Section: Introductionmentioning
confidence: 99%
“…25 Inhibition of MAP2K7 by 5Z7O induced apoptosis in T-ALL in a dose-dependent manner. 18 However, 5Z7O potently inhibits a variety of other kinases, including TAK1, which is a MAP3K. 26 Furthermore, 1 boasts only moderate potency against MEK7 (IC 50 = 1.3 μM).…”
mentioning
confidence: 99%
“…Additional assays confirmed a lack of binding at MEK3, MEK5, and MEK6 (Figure SI-1). Notably, 25 had no appreciable activity on MEK1/2, p38α/β, or JNK1/2/3, which are relevant kinases in our model for molecular pathophysiology in T-ALL. ,,, This compound also did not engage FLT3, a potential anticipated pitfall given the structural similarities between 25 and 5 , a reversible FLT3 inhibitor. MAP2K7 was not among the 90 wildtype kinases assayed and represented in Figure .…”
mentioning
confidence: 99%